Health in Peru 40 years after the Alma Ata Conference - Mascaro Sánchez, Pedro (2018)
On September 12, 1978, the WHO, UNICEF and 134 countries signed in Alma Ata (City of the Former Soviet Union) the declaration of primary health care (PHC), with the hope of achieving in the year 2000 'Health for All ' Although it is evident that the objectives set out in this commitment were not achieved in the proposed period, its approach has been an important milestone for Public Health in the world and has transcended the current context, since it established the need to build a new health system in the signatory nations,starting by defining the concept of health and its meaning as a state of physical, social and mental well-being, and not simply the lack of diseases or discomforts, placing it as a fundamental human right, in which other social and economic sectors must participate in addition to the health sector.